Physical changes to oil palm empty fruit bunches (EFB) and EFB Mat (Ecomat) during their decomposition in the field - Teh, Christopher Boon Sung; Goh, Kah Joo; Kamarudin, Khairun Nisa (Universiti Putra Malaysia Press, 2010)
The main objectives of this study were to determine the physical changes in oil palm empty fruit bunches (EFB) and EFB mat (Ecomat), which were used as soil mulching materials, during their decomposition in the field, as well as to compare the soil water content under these mulches and with bare soil. A field experiment was conducted at an estate using ten-year-old oil palm trees. Experimental design was a Randomized Complete Block with two treatments (EFB and Ecomat) and three replications. EFB was applied at 1000 kg palm-1 as a single layer on the soil surface. Ecomat was applied as a single layer with an area of 4 m2. Physical properties of EFB and Ecomat, measured every two month for six months, were bulk density, water content, water retention, and saturated hydraulic conductivity. Soil water content up to 750 mm depth was further measured on a daily basis. Results showed that EFB was better than Ecomat as a mulching material to conserve soil water. As compared to Ecomat, EFB had a lower bulk density (two times less dense), higher saturated hydraulic conductivity (about two times higher) and higher water content (between 20 to 57% more water). EFB was also found to hold its water more strongly than Ecomat. On average, the soil under EFB mulches had, nearly 27% more water than the soil under Ecomat mulches, and 38% more than bare soil. The soil under Ecomat mulches had only 8% more water than bare soil on average. Based on the model simulations, 5 layers of Ecomat would conserve as much soil water as 1 layer of EFB. Both mulching materials were estimated to fully decompose in the field in about 9 months.